Bioautographic profile of antimicrobial active extract from the stem barks of Entada spiralis Ridl - Mohd Hassan, Norazian; Mat So'ad, Siti Zaiton; Harun, Aiza; Wan Mat Khalil, Wan Khaima Azira; Che Mohd Ramli, Neni Kartini (2010)
Entada spiralis Ridl. which is locally known as Sintok or Beluru is a woody climber with a characteristic spiral stem. The stem bark is traditionally used as natural shampoo and body wash among Malays due to its high content of saponins and its medicinal properties. The methanol extract of the stem bark possess promising antimicrobial activity against some species of skin diseases caused microbes. A bioautographic profile as standard reference for qualitative analysis on the antimicrobial properties of E. spiralis stem barks was developed with the aim at validating the authenticity of the herbal material and quality control of its herbal preparations. A method of a combination of bioautographic assay and thin layer chromatography (TLC) analysis was employed to detect the antimicrobial biomarkers and to obtain the TLC profile, respectively. The methanol extract from the stem barks was fractionated through vacuum liquid chromatography to afford several fractions. Each fraction was assayed by Agar Disc Diffusion method and the active fractions were subjected to TLC analysis on silica gel plate. Five antimicrobial biomarkers were detected from the fractions by using bioautographic agar overlay assay against selected skin diseases caused bacterial and fungal strains, namely S. aureus, S. epidermidis, M. gypseum, T.mentagrophytes and T. tonsurans. The fraction which is eluted with methanol and chloroform at a ratio of 9:1 provides the best profile as standard reference for the efficacy analysis of E. spiralis as antimicrobial agent against skin infectious diseases microbes.